Acute Syphilitic Posterior Placoid Chorioretinitis: A Narrative Literature Review - Nikolina Andonova; Gueorgui Markov; Yani Zdravkov; Alexander Oscar (Sriwijaya Journal of Ophthalmology, 2022)
Acute syphilitic posterior placoid chorioretinitis (ASPPC) is defined by the presence of a placoid, yellowish, often solitary lesion, typically involving the areas of the temporal vascular arcades, the juxtapapillary retina, and/or the macular region, with the lesions being present at the level of the outer retina and retinal pigment epithelium (RPE). The visual acuity may range from no light perception to 20/20. There may be associated anterior chamber inflammation and vitritis. Therapy should include antibiotics for neurosyphilis. The role of corticosteroids is controversial. HIV coinfection should always be tested for. With appropriate therapy, the prognosis seems to be good.